Mycoplasma bovis antibody dynamics in naturally exposed dairy calves according to two diagnostic tests - Petersen, Mette Bisgaard; Wawegama, Nadeeka K.; Denwood, Matthew; Markham, Philip F.; Browning, Glenn F.; Nielsen, Liza Rosenbaum (BMC veterinary research, 2018)
Inexpensive and convenient diagnostic tests for use in clinical work and for the surveillance of infection with Mycoplasma bovis are in demand. The objective of this longitudinal field study was to gain knowledge about the dynamics of antibodies against M. bovis in sera from naturally exposed calves with and without different clinical signs, measured by two different ELISA tests. A total of 83 calves were subject to between one and five blood samples and clinical examinations using a standard protocol during five herd visits to each of four outbreak dairy herds. The blood samples were analysed for the presence of antibodies against M. bovis using the commercial IgG ELISA test BioX K302 (BioX) and an in-house indirect IgG ELISA test (MilA ELISA). Linear mixed models were used to describe and compare the antibody dynamics as measured by the two tests in relation to the disease status and age of the animals. The BioX ELISA response was below the recommended cut-off (37 ODC%) for the entire study period in many of the calves. The estimated mean ODC% increased slowly but did not reach the recommended individual animal cut-off in three of the four herds. The highest estimated ODC% was not reached until the calf was 110-130 days old. The MilA ELISA response rose above the recommended cut-off (135 antibody units (AU)) in almost all calves, and in two herds, the estimated mean was above the individual animal cut-off shortly after the birth of the calf. The highest estimated antibody concentration was reached when the calf was approximately 60 days old. Disease status of the calf was not significantly associated with the results of either test. We conclude that the BioX ELISA cannot be recommended for use in calves below 3 months of age. The MilA ELISA was able to detect antibodies shortly after birth (i.e. from approximately 3 weeks of age and onwards) and is therefore a more sensitive test for M. bovis exposure in young calves. Neither ELISA seemed able to differentiate between calves with arthritis and/or otitis media, and respiratory disease.